Inflammatory Bowel Disease : Diagnosis and Therapeutics - Cohen, Russell D. (Springer International Publishing : Imprint: Humana Press, 2017)
The latest edition of this text provides a comprehensive overview of the "natural flow of knowledge" regarding inflammatory bowel disease, with an emphasis on state-of-the art approaches that should be the basis for diagnosis and treatment of most patients. In addition to updated chapters, this volume includes new chapters on such topics as the impending biosimilar revolution, quality of care, and new challenges to previously held beliefs about IBD diagnosis, treatment, and pathogenesis. The book is also one of the first to have a chapter written specifically by and for physician extenders in the training of colleagues and the treatment of patients, which is of increasing importance moving forward in the medical profession. Written by experts in the field, Inflammatory Bowel Disease: Diagnosis and Therapeutics, Third Edition is a valuable resource for physicians, nurses, researchers, and other health care providers interested in the latest cutting-edge knowledge for treating patients with inflammatory bowel disease.
Keywords: Medicine.; Gastroenterology.; Pathology.; Rectum -- Surgery.; elektronické knihy; electronic books